KODE ETIK DALAM PROFESI KONSELOR BERDASARKAN ORGANISASI PROFESI BIMBINGAN DAN KONSELING (ABKIN) DAN ORGANISASI KONSELOR LAINNYA - Happy Karlina Marjo; Shabrina Zakira Nashrullah; Nur Syita Salamah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
The counselor profession has an important role in helping individuals overcome various emotional challenges and problems. In carrying out their duties, counselors are expected to adhere to a strict code of ethics, which guides their professional behavior. The code of ethics for counselors is established by the counselor professional institution. For the Indonesian territory, the code of ethics for counselors is determined by the Indonesian Counseling Guidance Association (ABKIN). A code of ethics is a guide or guideline for professional behavior or a moral foundation that is practiced, secured and upheld by counselors as members of professional organizations. This article explores aspects of the ABKIN code of ethics, codes of ethics of other counselor professions and compares the ABKIN Code of Ethics with codes of ethics issued by other counselor organizations, such as the American Counseling Association (ACA) in the United States. The method used in this research is a literature study with a qualitative descriptive approach. The data source comes from collecting documents in the form of books and previous research originating from various references. The data analysis technique used is descriptive analysis. The results of this research provide a better understanding of the importance of ethics in the counselor profession and illustrate how codes of ethics function as a guide to professional behavior for counselors based on regulations issued by several counselor organizations.